PENGARUH KEPRIBADIAN DAN LINGKUNGAN TERHADAP INTENSI BERWIRAUSAHA PADA USIA DEWASA AWAL - Eny Endah Pujiastuti (Asian Journal of Innovation and Entrepreneurship, 2013)
The challenge for University ini Indonesia is to foster entrepreneurial spirit by design (under planning), rather than by chance (by coincidence). One of the steps taken to overcome these problems is to foster the student entrepreneurial spirit. Therefore research on entrepreneurial intentions are very important because if students already have entrepreneurial intentions of students will then automatically open a business. One of them examines the factors that influence entrepreneurial intentions. Thus it is known that factors that influence the intention bewirausaha owned by someone other than internal factors, such as talent or innate nature (heredity), as well as a personality shaped by factors in the vicinity (external factors). This is evidenced also the results of research conducted at this time that the personality and the environment have an influence on entrepreneurial intentions.Keyword : jiwa kewirausahaan by design, kepribadian, lingkungan, intensi berwirausaha.